Design and simulation of polymer-based 1x4 asymmetric waveguide coupler - Mohd Shafiq, Mat Ghazali; Fadhlur Rahman, Mohd Romlay (2017)
The design and modelling of a 1x4 asymmetric waveguide couplers based on optical glue Epoxy OG142 is presented. The 1x4 asymmetric coupler is based on a cascaded design of a 1x2 Y-branch with two 1x2 asymmetric couplers. The design of the asymmetric coupler is based on asymmetric Y-junction splitter using tap-off ratio (TOFR) technique. This asymmetric design was achieved by varying the size of the tap line while the bus line was fixed at 1 mm size. A Y-branch and the 1x2 asymmetric couplers with different taper sizes have been designed using CAD tool and ray traced using non-sequential ray tracing. The designed TOFR for the 1x2 asymmetric coupler varies from 23% to 50% for tap line width of 300 um to 1000 um. Ray tracing models of various coupler design showed a linear relationship between the tap-off ratio (TOFR) and the waveguide tap width. The simulated ray tracing result shows TOFR values for the 1x4 asymmetric waveguide coupler varies from 23.1 to 50% for tap width of 300 um to 1000 um.